Thermodynamic Method for Measuring the B/A Nonlinear Parameter Under High Pressure - Piotr KIEŁCZYŃSKI; Marek SZALEWSKI; Andrzej BALCERZAK; Krzysztof WIEJA; Aleksander J. ROSTOCKI; Ryszard M. SIEGOCZYŃSKI (Engineering Transactions, 2014)
The nonlinearity parameter B/A is a measure of the nonlinearity of the equation of state for a fluid. The nonlinearity parameter B/A is a physical parameter often used in acoustics, from underwater acoustics to biology and medicine. It can provide information about structural properties of the medium, internal pressure and inter-molecular spacing. The thermodynamic method has been applied for determination of B/A parameter in diacylglycerol (DAG) oil as a function of pressure at various temperatures. Isotherms of the density and phase velocity of longitudinal ultrasonic wave as a function of pressure have been measured. Using the thermodynamic method along with measured isotherms of sound speed and density, the nonlinearity parameter B/A (for DAG oil) was evaluated as a function of pressure (up to 220 MPa) at various temperatures ranging from 20 to 50◦C.